Development of novel self-healable hydrogel for wound healing applications - Tjoang, Julia Stefanny (Nanyang Technological University, 2022)
Bullfrog skins have a high potential as a novel source of gelatin as it has some advantages when compared to commercial sources of gelatin (porcine and bovine). In this study, we synthesized bullfrog derived gelatin and fabricated a hydrogel from bullfrog gelatin and oxidized dextran (ODEX). The dynamic covalent bond between the bullfrog gelatin and oxidized dextran allows the hydrogels to have self-healing property. It is hypothesized that this property, combined with the similarity of gelatin and the extracellular matrix (ECM), will make an excellent wound dressing material. The storage modulus of the hydrogel fabricated (800-1600 Pa) were comparable to other hydrogels used for wound healing application. However, we found that the fabricated hydrogels had degraded completely within 3 days and human immortalised skin cells were unable to form a monolayer when seeded on top of the hydrogels, indicating that the chemical stability and cytocompatibility of the hydrogels need to be further improved.